Estimating the post-closure management time for landfills containing treated MSW residues. - Hall, D. H.; Gronow, Jan R.; Smith, Richard; Rosevear, Alan (Eurowaste, 2005)
The Landfill Directive will require the pre-treatment of MSW prior to landfilling. The removal of progressively increasing proportions of the biodegradable fractions from landfilled waste, and the UK Government’s commitment to increase recycling of key waste fractions, will lead to an inevitable change, from the disposal of raw MSW, to the disposal of MSW treatment residues, to landfill. This will undoubtedly change the type and rate of emissions from landfills. The question that this research project has sought to answer is “how long will active management be required for different MSW treatment residues?” The term equilibrium status has been used to define the end point beyond which management of wastes is no longer necessary. Calculating the equilibrium status of waste involves an assessment of the landfill gas emissions, leachate quality and hydraulic status of the landfill. These key parameters change with time as the landfill evolves. Equally, the engineering performance of a site is also changing with the gradual degradation of the liner and capping systems. The question posed above is therefore not easily answered.